Submicron silver-coated copper powder with low silver content and high coverage and a method for preparing the same
Patent Information
- Application Number
- CN202611178424.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]第一,银层致密性不足与界面结合力弱
[0038]银层覆盖率极高,银含量极低本发明通过“置换镀晶种+还原镀生长”的分步化学镀工艺,结合TEPA与EDTA–2Na复合络合剂对银离子定向沉积的协同调控作用,实现了银层在铜粉表面的均匀、致密生长。在银含量仅为20-25wt%的条件下,银层覆盖率可达98%以上,远优于传统置换法在同等银含量下60%-80%的覆盖率水平。
Smart Images

Figure CN122879684A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal powder processing technology, specifically to a submicron silver-coated copper powder with low silver content and high coverage, and its preparation method. Background Technology
[0002] Silver-coated copper powder, a core-shell composite powder material, retains the excellent electrical and thermal conductivity of silver powder while significantly reducing the amount of precious metals used by coating copper powder with a silver layer, making it an ideal alternative to pure silver powder. In recent years, silver-coated copper powder has been industrialized in the metallization process of heterojunction solar cells.
[0003] Currently, the main methods for preparing silver-plated copper powder include mechanical ball milling, chemical displacement, and chemical reduction. Among these, chemical silver plating is the most widely used due to its low cost and high efficiency. However, existing technologies still have the following prominent problems:
[0004] First, the silver layer lacks density and has weak interfacial adhesion. Traditional substitution methods suffer from insufficient silver coverage and a porous coating due to the mismatch in reaction kinetics between the copper substrate and silver ions. Especially under low silver content conditions, the silver layer is thin and easily detaches under mechanical stress from subsequent slurry rolling, leading to exposed copper cores and a sharp decline in oxidation resistance.
[0005] Second, the bonding strength at the silver-copper interface is insufficient. In silver-coated copper powder prepared by the chemical displacement method, the silver layer and the copper substrate are mainly physically attached, lacking a strong chemical or metallurgical bond, and the interface is easily peeled off under high temperature or mechanical stress.
[0006] Third, poor dispersibility and particle agglomeration. Submicron-sized copper powder has a large specific surface area and high surface energy, making it extremely prone to agglomeration during preparation and use, which affects the uniformity of the silver coating and the performance uniformity of the final product.
[0007] Fourth, insufficient high-temperature oxidation resistance. Existing low-silver-content silver-coated copper powder is prone to copper core oxidation at silver layer defects under high-temperature environments (such as sintering and heat treatment), resulting in a significant decrease in conductivity and reliability.
[0008] To address the aforementioned issues, researchers have attempted improvements by optimizing the complexation system, introducing an intermediate layer, or employing stepwise reactions. For example, using a composite complexing agent of tetraethylenepentamine (TEPA) and disodium ethylenediaminetetraacetate (EDTA–2Na) can improve the directional deposition of silver ions; adding a tin intermediate layer can enhance coating adhesion; and high-energy ball milling combined with heat treatment can strengthen interfacial bonding. However, these technical solutions mostly address only single problems and have not yet formed a systematic solution, often at the cost of sacrificing silver content control or process complexity.
[0009] Therefore, developing a submicron silver-coated copper powder with low silver content, high coverage, strong interfacial bonding, and excellent dispersibility, and its preparation method, has significant technological value and industrialization implications. Summary of the Invention
[0010] The purpose of this invention is to provide a submicron silver-coated copper powder with low silver content and high coverage, and its preparation method. Through synergistic optimization of three dimensions—chemical dimension (stepwise chemical plating + composite complexing agent control), structural dimension (tin interlayer construction), and physical dimension (ultrasonic-assisted dispersion + protective atmosphere heat treatment)—high density coating, strong interfacial bonding, and excellent high-temperature oxidation resistance of the silver layer are achieved under low silver content (≤25wt%) conditions.
[0011] The above-mentioned technical objective of the present invention is achieved through the following technical solution:
[0012] A method for preparing submicron silver-coated copper powder with low silver content and high coverage includes the following steps:
[0013] Step 1: Copper Powder Pretreatment
[0014] Submicron-sized spherical copper powder (average particle size 0.2-1.0 μm) was immersed in a dilute sulfuric acid solution (5%-10% by mass) for 5-15 minutes to remove the surface oxide layer and organic impurities. It was then washed with deionized water until neutral, and then washed with anhydrous ethanol 2-3 times. The washed copper powder was placed in a vacuum drying oven and dried at 30-40℃ for 6-12 hours to obtain pretreated copper powder.
[0015] Step 2: Copper powder surface micro-roughening treatment
[0016] Disperse the pretreated copper powder obtained in step one in deionized water, add an appropriate amount of surfactant (such as polyvinylpyrrolidone PVP, the amount added is 0.5%-2% of the copper powder mass), turn on the ultrasonic (power 200-500W, frequency 40kHz) and mechanical stirring (speed 300-600rpm), treat for 10-30min, so that the surface of the copper powder forms a micro-rough structure, which increases the mechanical interlocking points for subsequent silver layer deposition.
[0017] Step 3: Preparation of the tin plating intermediate layer
[0018] (1) Preparation of tin plating solution: Add 10-100g / L of thiourea, 10-80g / L of sodium hypophosphite and 5-20g / L of sodium citrate to a solution of stannous chloride dissolved in hydrochloric acid, stir evenly to obtain tin plating solution.
[0019] (2) Place the copper powder suspension obtained in step 2 in a constant temperature water bath and control the temperature at 40-60℃; under ultrasonic stirring, slowly drip the tin plating solution into the copper powder suspension and control the dripping time at 30-60 min; after the dripping is completed, continue the reaction for 20-40 min; after the reaction is completed, let it stand, filter, wash with deionized water until neutral, and vacuum dry at 40-50℃ to obtain tin-plated copper powder; the tin layer accounts for 8%-12% of the total mass of the composite powder.
[0020] Step 4: Step-by-step chemical silver plating
[0021] (1) Preparation of silver ammonia solution: Dissolve silver nitrate in deionized water, add appropriate amount of ammonia water to prepare silver ammonia complex solution, the concentration of silver ions is 0.05-0.2 mol / L; prepare a composite complexing agent solution, wherein the mass ratio of tetraethylenepentamine (TEPA) to disodium ethylenediaminetetraacetate (EDTA-2Na) is 1:2-2:1.
[0022] (2) Step 1 - Displacement silver plating (seed layer formation): Disperse the tin-plated copper powder obtained in step 3 in deionized water, add a composite complexing agent solution (the amount added is 0.5-1.5 times the theoretical amount of silver), and stir to mix evenly; take 2%-5% of the total silver amount of silver ammonia solution and slowly add it dropwise to the above suspension at a rate of 0.5-2 mL / min, and react at 20-30℃ for 1-3 h; during the reaction, continue to use ultrasound and mechanical stirring to make silver ions uniformly replace and form a nanoscale silver seed layer on the surface of copper powder.
[0023] (3) Second step - chemical reduction silver plating (silver layer growth): The remaining 95%-98% silver ammonia solution and reducing agent solution (glucose or hydrazine hydrate, concentration of 0.1-0.5 mol / L) are slowly added dropwise to the reaction solution of the first step in a parallel flow; the dropping time is controlled at 2-4 h, the temperature is slowly raised to 40-60 ℃ during the dropping process, and continuous ultrasonic and mechanical stirring is carried out; the dropping acceleration rate of the reducing agent solution is at least twice the dropping acceleration rate of the silver ammonia solution; after the reaction is completed, a silver-coated copper powder suspension is obtained.
[0024] Step 5: Post-treatment and heat treatment strengthening
[0025] (1) Centrifuge the silver-coated copper powder suspension obtained in step four, wash it with deionized water and anhydrous ethanol alternately 3-5 times to remove free silver ions and residual reactants; and vacuum dry it at 50-70℃ for 6-12 hours.
[0026] (2) Protective atmosphere heat treatment: The dried silver-coated copper powder is placed in a tube furnace and heated to 300-500℃ at a heating rate of 5-10℃ / min under an argon or nitrogen protective atmosphere (gas flow rate 100-300mL / min), and held at that temperature for 1-3 hours; after the holding period, it is cooled to room temperature with the furnace. During the heat treatment process, the silver layer, the tin intermediate layer and the copper substrate form a metallurgical bond through atomic thermal diffusion, which further strengthens the interfacial bonding force.
[0027] (3) Surface modification treatment: Disperse the heat-treated silver-coated copper powder in an ethanol solution containing 0.5%-2% oleic acid or stearic acid, and sonicate for 10-30 minutes to perform surface hydrophobic modification; then centrifuge, wash, and vacuum dry to obtain the final product.
[0028] Preferably, the submicron-sized spherical copper powder in step one has a purity of ≥99.9% and a particle size distribution D50 of 0.3-0.8μm.
[0029] Preferably, the tin layer in step three accounts for 10% of the total mass of the composite powder.
[0030] Preferably, in step four, the first step of silver replacement plating uses 2% of the total silver amount, and the feeding time is extended to 3 hours.
[0031] Preferably, the temperature of the protective atmosphere heat treatment in step five is 400°C, and the holding time is 2 hours.
[0032] The submicron silver-coated copper powder prepared by this invention has a three-layer core-shell structure of "copper core—tin intermediate layer—silver shell", wherein:
[0033] Copper core: average particle size 0.2-1.0 μm, spherical or near-spherical;
[0034] Tin interlayer: 5-15nm thick, accounting for 8%-12% of the total mass of the composite powder;
[0035] Silver shell layer: 20-50nm thick, accounting for 20-25% of the total mass of the composite powder;
[0036] Silver coverage ≥ 98%.
[0037] In summary, the present invention has the following beneficial effects:
[0038] This invention achieves uniform and dense silver layer growth on copper powder surfaces through a stepwise chemical plating process of "displacement seeding + reduction growth," combined with the synergistic regulation of silver ion directional deposition by a TEPA and EDTA-2Na composite complexing agent. With a silver content of only 20-25 wt%, the silver layer coverage can reach over 98%, far exceeding the 60%-80% coverage level of traditional displacement methods with the same silver content.
[0039] This invention introduces a tin interlayer between the copper core and the silver shell, enabling tin to form a good metallurgical bond with both copper and silver, significantly improving the interfacial bonding strength. Combined with subsequent heat treatment in a protective atmosphere at 300-500℃, a Cu-Sn-Ag gradient diffusion layer is further formed through atomic thermal diffusion, achieving a leap from physical adhesion to metallurgical bonding. Testing shows that the silver layer adhesion (critical load of the scratch test) of the silver-coated copper powder of this invention is approximately 200%-300% higher than that of the control sample without the interlayer. After multiple rolling processes of the slurry, the silver layer peeling rate is <1%, while the peeling rate of traditional products can reach 15%-30% under the same conditions.
[0040] The silver-coated copper powder prepared by this invention exhibits a weight gain of less than 2% after being oxidized at 300°C in air for 2 hours; while the silver-coated copper powder prepared by the traditional substitution method can achieve a weight gain of 10%-25% under the same conditions. After calcination at 600°C, the product of this invention still maintains good electrical conductivity. This is attributed to the barrier effect of the dense silver shell layer and tin interlayer, as well as the elimination of interface defects after heat treatment.
[0041] This invention incorporates the synergistic effect of ultrasonic-assisted dispersion and mechanical stirring throughout the preparation process, effectively suppressing the aggregation of submicron particles. Combined with surface hydrophobic modification in the post-processing stage, the product's dispersibility in organic carriers is significantly improved, making it suitable for applications such as high-precision screen printing.
[0042] This invention precisely controls the deposition location and amount of silver through a stepwise reaction, achieving a silver utilization rate of ≥95%, far exceeding the 70%-80% utilization rate of traditional methods. While achieving equivalent performance, the silver content can be reduced to 20-25 wt%, a reduction of more than 15% compared to traditional products (silver content above 30 wt%). Attached Figure Description
[0043] The invention will be further described below with reference to the accompanying drawings.
[0044] Figure 1 These are electron micrographs of submicron silver-coated copper powder with low silver content and high coverage. Detailed Implementation
[0045] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings.
[0046] The performance of this invention is verified through several embodiments and comparative examples.
[0047] Example 1
[0048] This embodiment provides a method for preparing submicron silver-coated copper powder with low silver content and high coverage, including the following steps:
[0049] Step 1: Copper powder pretreatment: Take 100g of spherical copper powder with an average particle size D50=0.5μm, soak it in 500mL of 8% dilute sulfuric acid solution for 10min; wash it with deionized water until neutral, wash it 3 times with anhydrous ethanol; and vacuum dry it at 40℃ for 6h.
[0050] Step 2, Surface micro-roughening treatment: Disperse the pretreated copper powder in 1000mL of deionized water, add 1.0g PVP (K30), turn on the ultrasonic treatment (power 350W, frequency 40kHz) and mechanical stirring (speed 450rpm), and treat for 20min.
[0051] Step 3, Tin Plating Intermediate Layer: Prepare the tin plating solution (thiourea 50g / L, sodium hypophosphite 40g / L, sodium citrate 12g / L dissolved in hydrochloric acid-dissolved stannous chloride solution). Place the copper powder suspension in a 50℃ constant temperature water bath, and add the tin plating solution dropwise under ultrasonic stirring for 45 minutes; continue the reaction for 30 minutes; filter, wash, and vacuum dry at 50℃ to obtain tin-plated copper powder (tin content approximately 10wt%).
[0052] Step 4: Step-by-step chemical silver plating:
[0053] (1) Prepare silver ammonia solution (Ag⁺ concentration 0.2mol / L, total silver content corresponds to silver content of 24wt% in silver-coated copper powder); prepare composite complexing agent solution (TEPA:EDTA–2Na=1:1, mass ratio).
[0054] (2) First step of displacement plating: Disperse the tin-copper powder in deionized water, add the composite complexing agent solution, and stir to mix; take 2% of the total silver content silver ammonia solution and slowly add it dropwise at a rate of 1 mL / min, and react at 25℃ for 2 h.
[0055] (3) Second step of reduction plating: The remaining 98% silver ammonia solution and 0.2 mol / L glucose solution were added dropwise in parallel for 3 hours and the temperature was raised to 50℃. After the reaction was completed, a silver-coated copper powder suspension was obtained.
[0056] Step 5, Post-treatment and heat treatment: Centrifuge and wash with deionized water and ethanol alternately 4 times; vacuum dry at 60℃ for 8h; place in a tube furnace, under argon protection (flow rate 200mL / min), heat to 400℃ at 8℃ / min, and hold for 2h; after cooling, disperse in 1% oleic acid ethanol solution and sonicate for 20min; centrifuge, wash, and dry to obtain the final product.
[0057] Testing revealed that the silver content of the silver-coated copper powder obtained in this embodiment was 23.6 wt%, the silver layer coverage was 98.5%, and the average particle size D50 was 0.52 μm.
[0058] Comparative Example 1 (Wuxi Intermediate Layer)
[0059] Except for omitting step three (tin plating intermediate layer), the preparation conditions are exactly the same as in Example 1.
[0060] Comparative Example 2 (non-step electroless plating)
[0061] The traditional one-step displacement method was used, in which all the silver ammonia solution was added to the copper powder suspension at once for reaction, and the other conditions were the same as in Example 1.
[0062] Comparative Example 3 (without heat treatment strengthening)
[0063] Except for omitting the protective atmosphere heat treatment in step five, the other preparation conditions are exactly the same as in Example 1.
[0064] Performance testing and data comparison
[0065] The following performance tests were performed on the silver-coated copper powders prepared in Example 1 and Comparative Examples 1-3:
[0066] (a) Silver coverage
[0067] The silver layer coverage was determined using energy dispersive spectroscopy (EDS) surface scanning combined with image analysis.
[0068] Table 1 Silver Coverage Table
[0069]
[0070] The results show that, under similar silver content conditions, the silver layer coverage of Example 1 of the present invention (98.5%) is significantly better than that of Comparative Example 2 (72.6%) and Comparative Example 1 (92.3%), indicating that the step-by-step electroless plating process and the introduction of the tin intermediate layer have a synergistic effect on improving the coverage.
[0071] The adhesion of the silver layer was tested using the scratch method and characterized by the critical load (Lc).
[0072] Table 2 Critical Load Table
[0073]
[0074] The results show that the bonding strength (28.6 N) of Example 1 of the present invention is 130.6% higher than that of the sample without Sn interlayer, 228.7% higher than that of the sample obtained by one-step replacement method, and 57.1% higher than that of the sample without heat treatment. The synergistic effect of the tin interlayer and the heat treatment process significantly enhances the interfacial bonding strength.
[0075] The high-temperature oxidation weight gain method was used: each sample was placed in an air environment at 300℃ for 2 hours for constant temperature oxidation, and the weight gain rate was measured.
[0076]
[0077] The results show that the high-temperature oxidation weight gain rate (1.8%) of Example 1 of the present invention is significantly lower than that of the comparative examples, indicating that the synergistic barrier effect of the tin interlayer and the dense silver layer effectively inhibits the high-temperature oxidation of the copper core.
[0078] Each sample was prepared into a conductive paste according to the same formula. After being rolled three times by a three-roll mill, the proportion of silver layer detachment area was statistically analyzed.
[0079]
[0080] The results show that the silver layer shedding rate of Example 1 after multiple rolling processes was only 0.8%, while that of Comparative Example 2 was as high as 28.4%, proving that the reliability of the product of the present invention in actual processing applications is far superior to that of the prior art.
[0081] The preparation method of this invention has a clear process route, is controllable, and is suitable for large-scale production. The prepared low-silver-content, high-coverage submicron silver-coated copper powder can be widely used in heterojunction (HJT) solar cell electrode paste, conductive adhesive, electromagnetic shielding coating, and MLCC capacitor electrodes, effectively reducing the consumption of precious silver and yielding significant economic and social benefits.
[0082] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall fall within the scope of the invention.
Claims
1. A method for preparing submicron silver-coated copper powder with low silver content and high coverage, characterized in that: Includes the following steps: Step S1: The submicron copper powder is subjected to acid washing pretreatment and surface micro-roughening treatment; Step S2: Chemically plate tin onto the surface of the pretreated copper powder to form a tin interlayer; Step S3: A stepwise chemical silver plating method is adopted. First, a silver seed layer is formed on the surface of tin-plated copper powder through a displacement reaction. Then, a chemical reduction reaction is used to make the silver layer grow densely on the seed. Step S4: The composite powder after silver plating is subjected to heat treatment in a protective atmosphere so that the silver layer, tin intermediate layer and copper core form a metallurgical bond through atomic diffusion. Step S5: Perform surface modification treatment on the heat-treated composite powder.
2. The method for preparing submicron silver-coated copper powder with low silver content and high coverage according to claim 1, characterized in that: In the stepwise chemical silver plating process, the first step, displacement silver plating, uses 2%-5% of the total silver amount, with a reaction temperature of 20-30℃ and a reaction time of 1-3 hours; the second step, chemical reduction silver plating, uses the remaining silver source, with a reaction temperature of 40-60℃ and a reaction time of 2-4 hours.
3. The method for preparing submicron silver-coated copper powder with low silver content and high coverage according to claim 1, characterized in that: The chemical silver plating process uses a composite complexing agent of tetraethylenepentamine (TEPA) and disodium ethylenediaminetetraacetate (EDTA–2Na) in a mass ratio of 1:2 to 2:
1.
4. The method for preparing submicron silver-coated copper powder with low silver content and high coverage according to claim 1, characterized in that: The mass of the tin interlayer is 8%-12% of the total mass of the composite powder.
5. The method for preparing submicron silver-coated copper powder with low silver content and high coverage according to claim 1, characterized in that: The protective atmosphere heat treatment is performed at a temperature of 300-500℃ for 1-3 hours, and the protective atmosphere is argon or nitrogen.
6. The method for preparing submicron silver-coated copper powder with low silver content and high coverage according to claim 1, characterized in that: The average particle size of the submicron copper powder is 0.2-1.0 μm.
7. The method for preparing submicron silver-coated copper powder with low silver content and high coverage according to claim 1, characterized in that: The mass of the silver shell layer is 20-25% of the total mass of the composite powder, and the silver layer coverage is ≥98%.
8. The submicron silver-coated copper powder with low silver content and high coverage as described in claim 1, and its preparation method, characterized in that: The electroless tin plating solution contains 10-100 g / L thiourea, 10-80 g / L sodium hypophosphite, and 5-20 g / L sodium citrate.
9. The submicron silver-coated copper powder with low silver content and high coverage as described in claim 1, and its preparation method, characterized in that: The preparation method is aided by ultrasonic and mechanical stirring for synergistic dispersion throughout the process.
10. A submicron silver-coated copper powder with low silver content and high coverage, characterized in that: The silver-coated copper powder with low silver content and high coverage as described in any one of claims 1 to 9 and the preparation method thereof are used to obtain the powder. The powder has a three-layer core-shell structure of "copper core - tin intermediate layer - silver shell", the silver content is 20-25 wt%, the silver layer coverage is ≥98%, and the weight gain rate after oxidation at 300℃ for 2 hours is ≤2%.